The F-Analogue of Riordan Representation of Pascal Matrices via Fibonomial Coefficients - Naim Tuglu; Fatma Yesil; E. Gokcen Kocer; Maciej Dziemiańczuk (Journal of Applied Mathematics)
We study an analogue of Riordan representation of Pascal matrices via Fibonomial coefficients. In particular, we establish a relationship between the Riordan array and Fibonomial coefficients, and we show that such Pascal matrices can be represented by an F-Riordan pair.